FAKTOR FAKTOR YANG MEMPENGARUHI PERSEPSI MAHASISWA TENTANG MATA KULIAH KEWIRAUSAHAAN - mirad, abdul; nurpeni, nurpeni; nielwaty, elly (FAKULTAS ILMU ADMINISTRASI UNIVERSITAS LANCANG KUNING, 2016)
This research was held with a period of study of 3 (three) months. Where the population and the sample amounted to 42 people consisting of morning class students of semester VII Fia Unilak. The sampling technique are using census. Type of data that collected in this study includes data, past experiences, beliefs, and experiences of others. the theoretical concepts using the concept of Vincent Gaspers. Analysis of the data in this study is using qualitative descriptive analysis. The research was funded by the Faculty of Administration with funds in the amount of three (3) million rupiah. The results of research is Pretty Good with responses as many as 18 respondents or 41.67% that responded Pretty Good which is the most dominant indicator of past experience as much as 19 respondents or 42 responses , 52%. Suggestions in this research is to create and provide views of the respondents who are young cadres in trying to run a business entrepreneur which must to remember the intense competition in the world of work so that entrepreneurship is the one of ways to go. And to all parties to work together to form a cadre of entrepreneurs who are reliable in the Lancang Kuning University Pekanbaru